Targeted Nanoparticles with High Heating Efficiency for the Treatment of Endometriosis with Systemically Delivered Magnetic Hyperthermia (Small 24/2022). Issue 24 (16th June 2022) - Park, Youngrong; Demessie, Ananiya A.; Luo, Addie; Taratula, Olena R.; Moses, Abraham S.; Do, Peter; Campos, Leonardo; Jahangiri, Younes; Wyatt, Cory R.; Albarqi, Hassan A.; Farsad, Khashayar; Slayden, Ov D.; et al.
Abstract : Endometriosis Treatment In article number 2107808, Ov D. Slayden, Oleh Taratula, and co‐worker develop an endometriosis therapy based on targeted magnetic nanoparticles that efficiently accumulate in endometriotic lesions following systemic administration, and specifically eradicate the disease by generating therapeutic temperatures inside the lesions upon exposure to an external alternating magnetic field.